Multi criteria decision making for assisting business angels in investments - Rostamzadeh, Reza; Ismail, Kamariah; Zavadskas, Edmundas Kazimieras (Technological and Economic Development of Economy, 2014)
The roles of business angels (BAs) are especially important in view of both decreasing the levels of formal venture capital investment and growing the average amount of individual deals. Angel investors typically invest at an earlier stage of growth and provide more business guidance than venture capital providers. Therefore, angel investors are the key players in generating high-growth companies, essential to regional economic development. As a result, they have attracted the attention of policy makers. Thus, this research attempted to improve the conception of decision-making criteria used by the BAs for investment, and reports the findings of an exploratory project that analysed the Malaysian BAs’ decision-making process. A hierarchy of multiple criteria decision making (MCDM) model based on fuzzy sets theory and VIKOR (in Serbian: Vise Kriterijumska Optimizacija I Kompromisno Resenje) method were proposed in order to look into the decision making process. For this reason, 5 main criteria and 29 sub criteria were developed to be evaluated by 5 well-known BAs to assess and rate the criteria and alternatives using fuzzy linguistic variables. For the purpose of illustration, an empirical case study was conducted on Malaysian BAs and the results are presented with numerical examples. The final finding of the research suggested that Johor is the most suitable city for investment. Kuala Lumpur, Penang, and Sabahare placed in the subsequent ranks. The proposed framework had been successfully applied for the decision making process, and could be used by other BAs for their cases with slight modifications.